DISCRITIVE STUDY ABOUT SUPERVISION TEACHING MATERIAL ON PORSPECTIVE PRINCIPAL TRAINING IN GUNUNG KIDUL YOGJAKARTA - Supriyana, Heri (Advances in Social Sciences Research Journal, 2018)
The objective of this research is to explore the relevancy, adequacy, consistency and the arrangement of supervision teaching material in Gunung Kidul, Yogjakarta. This research uses the descriptive research model which is to find the facts and interpretation accurately. The descriptive research model describes the characteristic individual or group phenomenon and also determines the frequency of events to minimize the bias and to optimize the reality. The result of this research from the data analysis, the means is 2.15 classified bad. It means that the relevancy of academic teaching material is low. It is not correlated to the everyday principal task.